Hubungan Antara Minat Baca Dengan Hasil Belajar Bahasa Indonesia Siswa Kelas V SD Negeri 107428 Teluk Ibus - Sri Agustin, Sujarwo (Pusdikra Publishing, 2022)
This research is quantitative which aims to link reading intereset with indonesian class students’learning outcomes V SD Negeri 107428 Teluk Ibus.This tyfe of research is to use qualitative methods of population correlation research in popolation correlation research in this study are all students V SD Negri 107428 Teluk Ibus school year 2021/2022.Popoulation consists of 31 students.Data colllection techniques for learning outcomes using questionnaires and documentation.The results of the study showed that the reading interest of the first grade students V SD Negri 107428 Teluk Ibus .Including very high dan their indonesian language learning outcomes are very correlation calculation result product moment shows that rhitung > rtabel (0,509 > 0,244).Large coefficient of determination (KD) is 0,26,This means that reading interest determines learning outcomes 26% whereas 74% .Other factors are determined by other factors .The large correlation between reading interset and indonesian language learning outcomes is included in the medium category ,it can be concluded that reading intersest has a relationship with indonesian students learning outcomes V SD Negri 107428 Teluk Ibus.It can be concluded that student’s reading interest is very influential in improving the learning outcomes of indonesian class students.